S139 A Paradoxical Rise In Rectus Femoris Myostatin (gdf-8) And Gdf-15 In Response To Neuromuscular Electrical Stimulation In Critical Care. (10th November 2014) - Bloch, SAA; Syburrah, T; Rosendahl, U; Kemp, PR; Griffiths, MJD; Polkey, MI
Abstract : Introduction: Neuromuscular electrical stimulation (NMES) is widely used in rehabilitation and muscle disease. Recently there is increasing interest in its use as a prevention and treatment for intensive care unit acquired weakness (ICUAW). ICUAW is a common and often devastating disease resulting as a consequence of critical illness. The molecular mechanisms are not understood, however early mobilisation and rehabilitation are to date the most effective treatments. NMES has been shown to help prevent muscle wasting in some clinical studies in the ICU setting, however the evidence is inconclusive. We hypothesised that the NMES of a single leg in critical care patients would be associated with reduced muscle wasting and down regulation of molecular pathways involved in muscle breakdown. Specifically myostatin (GDF-8), a potent negative regulator of muscle mass, and GDF-15, a potential novel driver of muscle atropy. Methods: We conducted a single-blinded, single leg, contralateral controlled trial of NMES in patients admitted to a specialist cardiothoracic ICU. Patients were recruited prior to elective high-risk cardiac surgery or during ICU admission. Baseline bilateral rectus femoris cross sectional area (RFcsa ) was measured by ultrasound and rectus femoris biopsies were taken. 2 × 1 hour sessions of NMES were then conducted for 1 week and ultrasound and biopsies were repeated. Biopsy specimens were examined for mRNA expression of genes of interest and results analysed in paired analysis relative to baseline. (NCT01321320 ). Results: 12 patients completed the study protocol. Myostatin and GDF-15 mRNA expression were both significantly elevated in NMES legs compared to baseline (p = 0.03 and p = 0.04 respectively), but remained unchanged in control legs. There was no significant change in RFcsa . Discussion: It is believed that NMES will have beneficial effects in the ICU setting in terms of preservation of muscle function. However it is recognised to also have potential to cause muscle damage. In the setting of sedated patients who cannot report pain or those in whom the nutritional and metabolic status of the muscle may be expected to be poor, researchers should be aware that NMES may promote muscle breakdown.